Motivations to exercise in young men following a residential weight loss programme conducted in National Service - a mixed methods study - Alexander Wilhelm Gorny; Mui Cheng Low; Andrew Arjun Sayampanathan; Farah Shiraz; Falk Müller-Riemenschneider (BMC, 2021)
Abstract Background Physical activity is a critical component of lifestyle interventions to reduce body weight and maintain weight loss. The goal of this study was to examine the motivations to exercise in young men following a 5-month residential weight loss programme conducted in the Singapore military as part of National Service. Methods We conducted a sequential mixed methods study starting with three focus groups comprising 21 programme instructors. Fifteen former programme participants aged 20.8 years (±1.4) with an average body mass index (BMI) of 29.3 kg/m2 (±4.6) were interviewed in-depth over a total duration of 9 h. Another 487 current programme participants aged 20.8 years (±1.1), BMI 27.1 kg/m2 (±2.6), completed a survey on weight loss, physical fitness, and motivations to exercise using the Behaviours Regulating Exercise Questionnaire (BREQ-3). Qualitative data was coded thematically using the six constructs of exercise motivation described by self-determination theory: amotivation, external, introjected, identified and integrated regulation and intrinsic motivation. Quotes from interviewees were cross-tabulated according to their weight maintenance trajectories. BREQ-3 responses were analysed according to initial body mass index (BMI), percentage weight loss and fitness. Results Over the course of the residential programme interview and survey participants experienced an average weight loss of 15.6 kg (±6.5) and 13.0 kg (±5.4) respectively. Among the fifteen interviewees seven had gained no more than 34% of initial weight loss 6 months after completing the programme while another eight had gained more than 51%. We elicited three key themes from the data: (1) Barriers to exercise; (2) diminishing extrinsic motivation; and (3) unidentified exercise benefits. The integration of findings uncovered reinforcing motivational patterns in the areas of health, fitness, camaraderie and identified regulation. Narratives of self-acceptance and shift-work environments gave rise to potentially deleterious motivational patterns. Our findings suggest that successful transition from a residential programme to independent weight management requires a more deliberate pivot from predominantly extrinsic to intrinsic motivational approaches. Conclusion Residential programmes such as the one investigated here, should develop a deliberate transition strategy, replace weight loss targets with physical performance goals and promote sports that are appropriate for young men affected by overweight and obesity.